2020
DOI: 10.1007/s00411-020-00843-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of antioxidative effects between radon and thoron inhalation in mouse organs

Abstract: Comparison of antioxidative effects between radon and thoron inhalation in mouse organsBackground: Radon therapy has been traditionally performed globally for oxidative stressrelated diseases. Many researchers have studied the beneficial effects of radon exposure in living organisms. However, the effects of thoron, a radioisotope of radon, have not been fully examined. Objective: In this study, we aimed to compare the biological effects of radon and thoron inhalation on mouse organs with a focus on oxidative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 25 publications
(25 reference statements)
1
11
1
Order By: Relevance
“…Therefore, we examined key factors of the anti-oxidative system in the in vivo exposed animals using qPCR. However, unlike other reports [ 14 , 15 , 16 ], that indicated a significant influence of radon exposure especially on SOD1, we found no significant radon induced alterations of the anti-oxidative enzymes SOD1, GPx1, catalase, and Nrf2 in in vivo exposed animals ( Figure 2 ). This discrepancy is most likely due to the differences in experimental set-up (dose and duration of radon treatment), time of sampling (7d vs right after exposure), differences in utilized methods, the organs that have been looked into, and the mouse model used.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Therefore, we examined key factors of the anti-oxidative system in the in vivo exposed animals using qPCR. However, unlike other reports [ 14 , 15 , 16 ], that indicated a significant influence of radon exposure especially on SOD1, we found no significant radon induced alterations of the anti-oxidative enzymes SOD1, GPx1, catalase, and Nrf2 in in vivo exposed animals ( Figure 2 ). This discrepancy is most likely due to the differences in experimental set-up (dose and duration of radon treatment), time of sampling (7d vs right after exposure), differences in utilized methods, the organs that have been looked into, and the mouse model used.…”
Section: Discussioncontrasting
confidence: 99%
“…Next to the known analgesic effects, some hints on underlying molecular mechanisms have already been shown in pre-clinical models and patient studies. Among the most prominent findings in pre-clinical studies were discoveries concerning alterations of the anti-oxidative system with special emphasize on superoxide dismutase (SOD)1 as a key molecule [ 13 , 14 , 15 , 16 , 17 , 18 ] and in the immune system. For the latter, Nagarkatti et al reported an alteration of T cell numbers after radon exposure in lymphoid organs of mice as well as alterations in the numbers of lymphocytes and macrophages [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SOD activity and t-GSH levels were found to be significantly increased, whereas the LPO level was significantly decreased. (23) The phenomena were generally observed with radon inhalation of 2,000 Bq/m 3 and thoron inhalation of 500 Bq/m 3 . Difference in the optimal concentration could be attributed to the difference in radioactivity characteristics, such as emitted energy and half-life.…”
Section: Combined Use Of Radon Inhalation and Pregabalin Admin-mentioning
confidence: 97%
“…Therefore, thoron ( 220 Rn; Tn), a radioisotope of radon, may be useful for reproducing an artificial radon treatment environment. Interestingly, we previously reported that thoron inhalation also has antioxidative effects [ 9 ]. Our findings suggested that thoron inhalation could be used for the treatment of ROS-related diseases.…”
Section: Introductionmentioning
confidence: 99%